Pencegahan Diabetes Mellitus melalui Pemeriksaan Gula Darah Acak dan Promosi Kesehatan di Masyarakat - Ahmadi, Ahmadi; Lestari, Mei; Widyyati, Ika (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Diabetes Mellitus is a health problem that is increasing in prevalence throughout the world. This is of serious concern because of its far-reaching impact on public health and the health system as a whole. Objective: The purpose of this service was Increase access to public health services, especially in diabetes mellitus examination, in addition to increasing public knowledge about diabetes mellitus management. Method: Activities are carried out in several stages, namely the preparation stage includes taking care of permits, the next stage is the implementation of carrying out random blood sugar checks and health promotion. Result: It was found that respondents who carried out the examination were found to have mostly high random blood sugar values as many as 15 respondents or 62.5%. There was a significant change in knowledge from before and after health promotion Conclusion: The community has a potential risk of undetected diabetes mellitus, therefore the participation of health workers is needed to provide counseling. Through counseling delivered by health workers, the public can be given a better understanding of risk factors, symptoms, and ways to prevent diabetes mellitus